Back to the future - Andrija Mohorovičić lecture (1909) & Zagreb (2020) M5.5 earthquake - Stanko, Davor (Array, 2020)
This review paper relates original Mohorovičić, A. lecture DJELOVANJE POTRESA NA ZGRADE (1909, 1911) and its English translation EARTHQUAKE EFFECTS ON BUILDINGS (2009) with M5.5 Zagreb 2020 earthquake damage. Mohorovičić said in Introduction of his lecture in 1909: “another strong earthquake is needed to remind people that the building techniques should be further developed and improved…”. Oliver Wendell Holmes (1809-1894) said once: “The young man knows the rules, but the old man knows the exceptions”. This should remined us that going Back to the Future after strong earthquake, we must go Back to the Past, and look after Mohorovičić’s 15 rules how to build earthquake-resistant buildings. He tells us how to build, and unfortunately, we were left unprepared again and didn’t listen wisdom words of an “old man”.